# algebra

posted by .

I am having a hard time - please guide me to solve by the substitution method.
5m + n = 36
m -7n = 36

A big ty:)

• algebra -

Since m = 7n + 36,
substitute 7n + 36 for m in the first equation.

That should lead to
35n + 180 + n = 36
which is the same as
36n = -144
n = -4
Now solve for m with either of your first two equations.

## Similar Questions

1. ### Substitution Method-Plz help

Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get it.How …
2. ### Algebra II

How do you solve the linear equations x+y=5 3x-y=3 by use of the Substitution Method?
3. ### algebra

Solve by elimination method. 2r-5s=-33 5r+2s=48 Solve by substitution method. 5x+6y=5 x-9y=40 I always get these two confused... can someone please help me with these two problems?
4. ### Linear Equations

Can you please help solve this equation using the substitution method?
5. ### substitution method

Solve by substitution method please help me solve this. I do not know how to do this at all. The question is 3x+8y=33 and x=31-6y I know that I have to plug x into the first x like 3(31-6y)+ 8y = 33 but i do not know what to do from …
6. ### algebra

use the Substitution Method. Please give it a try. y = 3x + 4 5x + 3y = 12 Why is the substitution method preferred in this case?
7. ### algebra

solve by the substitution method: 8m+n=47 m-5n=52 thank you having trouble completing please show all work so I can learn better
8. ### Math

I still don't know how to directly solve this problem. Can someone guide to solve this system of equation by using the substitution method?
9. ### Algebra 1

bobpursey, In this problem you helped me with earlier: Solve using any appropriate method. y = 2× - 5, y = ½× + 1 Substitution, substitute for y. 2×-5=½ × + 1 3/2 x=6 x=4 y= 2*4-5=3 How did you choose which method you were going …
10. ### Algebra

Please solve using substitution method. 2n-11=m/4 n=m/-3

More Similar Questions